Civilian Attitudes of Russian Students in the Context of a Special Military Operation - V. A. Smirnov (Высшее образование в России)
The article analyzes individual elements in the structure of civil attitudes of Russian students in the situation of the beginning and continuation of a special military operation (SVO). A special military operation acts as a kind of “litmus test”, which allows to identify the features of the civic consciousness of students, since it is in a crisis situation that latent value attitudes that determine social and civic behavior are actualized. The article is based on the results of an empirical sociological study. The study sample is quota– based, stratified by gender, the sample size is 1,380 people aged 18 to 22 years. As a result of the conducted research: the polarization of Russian students in terms of attitude to a special military operation is justified; the conclusion is made about the “background” nature of the SVO for a significant part of the student youth; the influence of ITS on the growth of stress among students faced with its results has been proven; the hypothesis about the influence of the SVO on the dynamics of civil attitudes of Russian students is confirmed. In particular, a special military operation has an impact on reducing students’ trust in socio-political institutions and actors, and also affects the dynamics of migration sentiments, increasing the percentage of young people considering migration as a possible option for a life trajectory. The study demonstrated the need for further study of the stability of the civic attitudes of Russian youth in the context of the escalation of “new” cognitive wars, as well as an analysis of the effectiveness of state institutions of socialization in a situation of geopolitical instability.